Kalian Pembentukan Hukum Internasional di Komite Antariksa Perserikatan Bangsa-Bangsa (PBB) (Lex Jurnalica, 2011)
United Nations Commiteee on Peaceful Uses of Outer Space (UNCOPUOS) is the first of United Nations Committee which apply using consensus procedures in adopt its decisions.  The result of the Committee and the both Subcommittee (Scientific and Technical Subcommitee and Legal Sub-commitee) use this method in adopting five United Nations Treaties on Outer Space and become positive international space law and  have been ratified by some States.  There are several challenge for the implementing of this method such as having much times to make every decisions.  This paper investigates how to implement this method in making decisions.This type of research is a normative study.Keywords:  International law, United Nation, Outer Space